Peritoneal dialysis associated-peritonitis: a preventable complication - de Miguel-Ibañez, Regina; Ramirez-Ramirez, Carlos Alberto; Sanchez-Gonzalez, Marcos Daniel; Ortiz-Bello, Angel Cesar (International Journal of Research in Medical Sciences, 2021)
Peritoneal dialysis is useful renal replacement therapy for patients with end-stage chronic kidney disease. Latin America has 30% of the world population in peritoneal dialysis and within these countries Mexico covers 73% of them. In our country, the Mexican institute of social security (IMSS by its Spanish acronym) serves more than half of the Mexican population that requires renal replacement therapy. In 2014 it represented 15% of total annual cost of the institution. Peritonitis in peritoneal dialysis is the main complication seen in this renal replacement therapy with morbidity and mortality from 2 to 6%. The epidemiology of peritonitis associated with peritoneal dialysis varies according to the continent, country and dialysis center. The rate of peritonitis per year of each center reflects their quality of care. The prevention, diagnosis and treatment of peritonitis impact in the quality of life of the patient, the success of renal replacement therapy, public health costs and associated mortality. This review addresses the epidemiology, diagnosis, treatment, and preventive measures of peritonitis, focused on the procedures for improving the standards of care.